Limit of a monotonically increasing sequence and decreasing sequence

If a sequence ($a_n$) is monotonically increasing, and ($b_n$) is a decreasing sequence, with $\lim_{n\to\infty}\,(b_n-a_n)=0$, show that $\lim a_n$ and $\lim b_n$ both exist, and that $\lim a_n=\lim b_n$.

My attempt:

To show that the limits of both sequences exist, I think I should be using the Monotone Convergence Theorem (MCT). For that I would need to show that the sequences are bounded.

($a_n$) is increasing, and so it should be bounded below. ($b_n$) is decreasing, so it should be bounded above. The challenge here is to show that ($a_n$) can be bounded above and ($b_n$) can be bounded below. This should utilise the third condition, from which I get:

& \lim_{n\to\infty}\,(b_n-a_n)=0 \\[3pt]
\iff & \forall\varepsilon>0,\ \exists N\in \mathbb{N} \text{ s.t. } \forall n\geq N,\ |{b_n-a_n}|<\varepsilon

I then tried using the triangle inequality:
$$ |b_n|-|a_n|\leq|b_n-a_n|<\varepsilon$$

but I’m not sure where to go from here.

Solutions Collecting From Web of "Limit of a monotonically increasing sequence and decreasing sequence"

The leftmost part of the inequality $|b_n|-|a_n|\leq|b_n-a_n|<\epsilon$ isn’t needed in the proof.

Claim 1     $(a_n)$ is bounded above.

Proof    Let $\epsilon>0$. From $|b_{n+1}-a_{n+1}|<\epsilon$, $a_{n+1}<b_{n+1}+\epsilon$. Use the monotonicity of $(a_n)$ and $(b_n)$. We have
$$a_1 \le \dots \le a_n\le a_{n+1} < b_{n+1}+\epsilon \le b_n+\epsilon \le \dots \le b_1 + \epsilon.$$
Since the choice of $n$ in the above inequality is arbitrary, we have $a_n < b_1 + \epsilon$ for all $n \in \Bbb N$.
Therefore, $(a_n)$ is bounded above by $b_1 + \epsilon$.

Similarly, we have another claim.

Claim 2     $(b_n)$ is bounded below.

Now, recall that $(a_n)$ and $(b_n)$ are increasing and decreasing sequences respectively, and apply MCT to $(a_n)$ and $(b_n)$ to establish the existence of $\lim a_n$ and $\lim b_n$. Finally, use $\lim\limits_{n\to+\infty}(b_n-a_n)=0$ to conclude that $\lim a_n = \lim b_n$.

Sorry for using others’ ideas in my solution. I would like to draw a commutative diagrams in the comments, but the system forbids me from posting comments with two or more @ characters, so I can’t post the following diagram in a comment. Hoping that others can benefit from his answer at the first glance, I draw this diagram for fun.

A graphical explanation to DonAntonio’s answer

@. a_n \\
@. @AA \vdots A \\
@. a_{N+1} \\
@. @AA (a_n)\uparrow A \\
@. a_N \\
\text{Suppose }a_N > b_K. \\
b_K @. \\
@V(b_n)\downarrow VV @.\\
b_{K+1} @. \\
@V \vdots VV @.\\
b_n @.
It’s clear from the diagram that we have to take $n \ge \max\{K,N\}$.
But $\lim\limits_{n\to+\infty}(b_n-a_n)=0$, contradiction.


Suppose there exists $\;K\in\Bbb N\;$ such that for some $\;N\in\Bbb N\;,\;\;a_N>b_K\;$ , say $\;a_N-b_K=\epsilon>0\;$ , but then

$$\forall\,n\ge N\,,\,\,\forall\,m\ge K\;,\;\;\begin{cases}a_n\ge a_N>b_K,&\text{since $\,\{a_n\}\,$ is monotone ascending}\\{}\\
b_m\le b_K<a_N,&\text{since $\,\{b_n\}\,$ is monotone descending}\end{cases}$$

and from here we’d get that for any $\;n\ge\max\,\{K,N\}\;$ :

$$a_n\ge a_N>b_K\ge b_n\implies a_n-b_n>\epsilon>0\implies \lim_{n\to\infty}(a_n-b_n)\neq0$$

and the above shows not only both sequence are bounded in the right direction, but also that they both bound each other resp.

You choose an $\varepsilon>0$ and have
$$|(a_n-b_n)|\lt\varepsilon, \forall n> N_0$$
because $\lim (a_n-b_n)=0$. To finish your proof, assume that $\lim a_n=a$ and $\lim b_n=b$. Then you have
$$|a_n-a|<\varepsilon, \;\forall n>N_1$$
$$|b_n-b|<\varepsilon, \; \forall n>N_2$$
So select an $n$ such that $n>N_0, n>N_1, n>N_2$ to get
$$|a-b|\le|a-a_n|+|a_n-b_n|+|b_n-b|\lt 3\varepsilon$$

$\varepsilon$ was chosen arbitrary therefore

Since $\lim_{n\to\infty}(b_n-a_n)=0$, there is an $N$ such that $|a_n-b_n|<1$ for all $n\ge N$. ($1$ is a number that I have just chosen for $\varepsilon$.) Since $b_n$ is decreasing, we have $a_n<b_n+1\le b_N+1$ for all $n\ge N$. Therefore $a$ is bounded from above, indeed by $\max\left\{a_0,a_1,\dots,a_{N-1},b_N+1\right\}$.

Therefore $a$ converges. Since $b_n = a_n + (b_n-a_n)$ and both $a$ and $b-a$ converge, $b$ also converges.